2012
DOI: 10.1100/2012/286741
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Image Encryption Algorithm Based on DNA Subsequence Operation

Abstract: We present a novel image encryption algorithm based on DNA subsequence operation. Different from the traditional DNA encryption methods, our algorithm does not use complex biological operation but just uses the idea of DNA subsequence operations (such as elongation operation, truncation operation, deletion operation, etc.) combining with the logistic chaotic map to scramble the location and the value of pixel points from the image. The experimental results and security analysis show that the proposed algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 16 publications
(15 reference statements)
1
43
0
Order By: Relevance
“…The correlation between the adjacent pixels of the encrypted images optimal and is close to zero. It is found that the obtained values are better than the methods in [10,15,20,21], comparable with those methods in [13,14,23] and slightly lesser than the method in [1]. The pictorial view of relationship between the adjacent pixels in horizontal, vertical, and diagonal directions in the original and encrypted Lena images are shown in Figure 8.…”
Section: Correlation Analysismentioning
confidence: 67%
“…The correlation between the adjacent pixels of the encrypted images optimal and is close to zero. It is found that the obtained values are better than the methods in [10,15,20,21], comparable with those methods in [13,14,23] and slightly lesser than the method in [1]. The pictorial view of relationship between the adjacent pixels in horizontal, vertical, and diagonal directions in the original and encrypted Lena images are shown in Figure 8.…”
Section: Correlation Analysismentioning
confidence: 67%
“…In this paper, we need only to refer to the GENE BANK once for key generation in comparison with indexed based method et al [4], where every time the database is required to be referenced for DNA sequence. There are total 8 kinds of the DNA coding to meet the complementary rule, and there are altogether 6 kinds of legal complementary rules to be applied, which make the algorithm more secure.…”
Section: Bio-securitymentioning
confidence: 99%
“…Various operations performed on DNA include synthesis, insertion, truncation, deletion, transformation, ligation and polymerase chain reaction etc. Qiang Zhang et.al [4] proposed an encryption method that used DNA subsequence operations such as truncation, deletion and transformation operation combined with chaos system to scramble the location and value of image pixel. Encryption method proposed by Nirmalya Kar et al [5] used DNA sequencing along with cryptographic algorithm to generate the cipher text similar with the biological structure of the DNA Strands.…”
Section: Introductionmentioning
confidence: 99%
“…Choose two random integers n, ∈ Z + and set L ← n · ; 15 Slice C into n sub-cipher messages C 1 , C 2 , . .…”
Section: Algorithmmentioning
confidence: 99%
“…The ancient Greeks also used to write in tablets and cover them by wax. Nowadays the steganography methods have developed a lot using digital cover medium carrier such as videos, audios, images [5], [15], text files, TCP/IP headers, documents and DNA steganography [1]. The DNA steganography explores and exploits DNA molecular techniques to hide information.…”
Section: Introductionmentioning
confidence: 99%